PEMBELAJARAN TERPADU TIPE WEBBED UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Evy Marita Yuliwinarti; Neni Mariana; Suryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning atmosphere is less pleasant and can not affect student learning outcomes, so it is necessary to apply a learning model that is able to create effective learning and can improve student learning outcomes. This study aims to implement integrated learning webbed type to improve students learning outcomes. This type of research is a classroom action action. The subjects of this study were students in grade VI SDN Wonocolo 2 consisting of 13 people. The data technique in this study is to provide learning outcomes tests. The data obtained were analyzed using quantitative analysis techniques. The results of this study were that in cycle I, there were 5 students who got a score of ≥ 65 with an average score of 57.30, while in the second cycle there were 13 students who obtained a score of ≥ 65 with an average score of 74, 23. Conclusion This research is the implementation of integrated learning webbed type can improve the learning outcomes. The implication of this research is to improve students' understanding of concepts through learning that is fun and easy to understand, can develop cognitive and psychomotor skills of students, and can increase student motivation to learn.